Statistical mechanics of liquids and solutions : intermolecular forces, structure and surface interactions - Kjellander, Roland, 1948- (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2020)
"The statistical mechanical theory of liquids and solutions is a fundamental area of physical sciences with important implications for many industrial applications. This book shows how you can start from basic laws for the interactions and motions of microscopic particles and calculate how macroscopic systems of these particles behave, thereby explaining properties of matter at the scale that we perceive. Using this microscopic, molecular approach, the text emphasizes clarity of physical explanations for phenomena and mechanisms relevant to fluids, addressing the structure and behavior of liquids and solutions under various conditions. A notable feature is the author's treatment of forces between particles that include nanoparticles, macroparticles, and surfaces. The book also provides an expanded, in-depth treatment of polar liquids and electrolytes"--
Statistical mechanics from a quantum perspective -- Classical statistical mechanics -- Illustrative examples from some classical theories of fluids -- Interaction potentials and distributions functions -- Interactions and correlations in simple bulk electrolytes -- Inhomogeneous and confined simple fluids -- Surface forces.
Keywords: Statistical mechanics; Kinetic theory of liquids